Sensorless Control of a PMSM Drive Using EKF for Wide Speed Range Supplied by MPPT Based Solar PV System - Anwer, Abbas Mahmood Oghor; Omar, Fuad Alhaj; Bakir, Hale; Kulaksiz, Ahmet Afsin (Elektronika ir Elektrotechnika, 2020)
In photovoltaic (PV) applications, employing Surface-Mounted Permanent Magnet Synchronous Motor (SMPMSM) can be a suitable option, especially for solar pumping and Heating, Ventilation, and Air Conditioning (HVAC) applications. However, when the motor loads are supplied from varying and limited energy sources, such as solar PV, it is vital to determine operating behavior and provide a stable operation for a wide range of operating conditions. In this study, the operating stability of Permanent Magnet Synchronous Motor (PMSM) was improved by sensorless Field Oriented Control (FOC) based on Extended Kalman Filter (EKF). In order to achieve optimal operation of the PV system under various meteorological conditions and load variations, an incremental conductance approach based maximum power point tracking (MPPT) system was introduced. For estimation of the speed of PMSM in wide speed range, instead of using a hybrid estimation strategy, fixed d-axis current with EKF was applied to the low-speed regions of SMPMSM, while in the medium and high speed regions, the d-axis current was set to zero. The major contributions of this paper are to reduce complexity of the control method and testing the method in a photovoltaic system with MPPT operation. The complete system was modeled in a Matlab/Simulink environment and simulation results are shown according to a wide range of operating conditions.